(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Ayurveda health tourism is emerging as a niche segment in the tourism landscape across the world. Ayurveda wellness therapies provide holistic and long-lasting health benefits to health and wellness seekers. The preventive, curative, relief and rehabilitative nature of ayurveda coupled with culture, tradition and local services provide various tangible and intangible benefits to tourists who demand such tourism services from ayurveda health Centres. Ayurveda is practised in its purest form in the Indian state of Kerala which inherited the traditional ‘Vaidya’ system of ayurveda, scenic beauty, the blend of tourist attractions and rich cultural heritage. The ayurveda health Centres in Kerala are emerging as the hub of wellness Centres with global access and brand image. The paper looks into various types of benefits received by Ayurveda health tourists visiting ayurveda Centres in southern Kerala. Data was collected from 500 health tourists using a structured interview schedule on 28 tourism attributes using 5 point Likert scale during the period September to April 2019. The important factors influencing the benefits of wellness tourists are identified through explorative factor analysis. Health outcome, Uniqueness, Novelty, Mental well-being and Physical appearance are the benefit factors identified in this study. The benefits identified in the study are important in designing customized services and expanding the health tourism market in Kerala.